The Cambridge history of American foreign relations - Perkins, Bradford (Cambridge : Canterbury University Press, 1993)
Volume I -- The Creation of a Republican Empire, 1776-1865.
Keywords: United States -- Foreign relations -- 1783-1815.; United States -- Foreign relations -- 1783-186.; United States -- Foreign relations -- To 1865.